Pengaruh Dimensi Kualitas Pelayanan Jasa Terhadap Kepuasan Pelanggan D&I Skin Centre Denpasar - Putri, Kadek Indri Novita Sari; Nurcaya, I Nyoman (E-Jurnal Manajemen, 2013)
This research has the objective to determine the effect of service quality dimensions on customer satisfaction and to determine which variables are dominant of the D & I customer satisfaction Skin Centre. The samples used in this study is accidental sampling, taken from the number of visits D & I Skin Center in 2011. The data were analyzed using SPSS 13.0 for Windows. Analysis of the data used is a confirmatory factor analysis and multiple linear regression analysis. Partial results showed significant effect between service quality (tangibles, reliability, responsiveness, assurance and empathy) to the D & I customer satisfaction Skin Centre. Keywords : Dimensions of Service Quality, Customer Satisfaction